MARKETING POLITIK PETAHANA SYARIF FASHA-MAULANA DALAM PEMILIHAN KEPALA DAERAH KOTA JAMBI PADA TAHUN 2018 - Santosa, Budi (Jurusan Ilmu Sosial dan Ilmu Politik Fakultas Hukum Universitas Jambi, 2019)
This research was conducted to find out how the strategies carried out by Petahana Syarif Fasha and Maulana in order to compete in the regional head elections of Jambi City in 2018 aimed at winning the elections. In this study the author uses a type of qualitative research and structured interviews to people who are considered to know about what they want to study, such as incumbent Syarif Fasha, Dr. Maulana, Success Team, Supporting Party and Community of Jambi City. The results of this study indicate that the strategy (Political Marketing) of the partners of Petahana Syarif Fasha and Maulana uses Firmanzah's Political Marketing theory. In the preparation and strategy of winning the couple, they were greatly helped by the Firmanzah theory, namely 4S: Product, Promotion, Price and Place. The strategy (Political Marketing) can be effective and efficient in achieving a victory in the Regional Head Election of Jambi City in 2019.